2023
DOI: 10.3390/ijms24086978
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Diabetes

Abstract: Diabetes is the most common metabolic disorder, with an extremely serious effect on health systems worldwide. It has become a severe, chronic, non-communicable disease after cardio-cerebrovascular diseases. Currently, 90% of diabetic patients suffer from type 2 diabetes. Hyperglycemia is the main hallmark of diabetes. The function of pancreatic cells gradually declines before the onset of clinical hyperglycemia. Understanding the molecular processes involved in the development of diabetes can provide clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 207 publications
0
9
0
Order By: Relevance
“…The inverse association between DRRD and renal cancer risk in the study may be explained by the following mechanisms. It is known that diabetes is a metabolic disease characterized by chronic hyperglycemia, and the development of diabetes mainly includes the following three aspects: insulin resistance, pro-inflammatory effect, and compensatory excessive insulin production [ 39 ], which exhibits overlapping mechanisms with renal cancer [ 4 ]. First, insulin can directly or indirectly regulate the production of hepatic IGF-1 [ 40 ], and relevant clinical research has confirmed that elevated serum IGF-I levels are linked to a greater risk of renal cancer [ 6 , 7 ] and that insulin resistance further enhances the above effects [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inverse association between DRRD and renal cancer risk in the study may be explained by the following mechanisms. It is known that diabetes is a metabolic disease characterized by chronic hyperglycemia, and the development of diabetes mainly includes the following three aspects: insulin resistance, pro-inflammatory effect, and compensatory excessive insulin production [ 39 ], which exhibits overlapping mechanisms with renal cancer [ 4 ]. First, insulin can directly or indirectly regulate the production of hepatic IGF-1 [ 40 ], and relevant clinical research has confirmed that elevated serum IGF-I levels are linked to a greater risk of renal cancer [ 6 , 7 ] and that insulin resistance further enhances the above effects [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…IR refered to the decreased sensitivity of peripheral tissues (mainly liver, fat and adipose tissues) to insulin action caused by various reasons, which reduced the efficiency of insulin in promoting glucose uptake and utilization. Upon the onset of IR, there is an elevation in oxidative stress (OS) within islet β cells and peripheral tissues, resulting in impaired insulin secretion, and the development of T2DM [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes is a metabolic disorder with hallmarks of insulin resistance and hyperglycemia, closely related to other chronic diseases ( Guo et al, 2023 ). The main trigger is excess glucose accumulation originating from the carbohydrate-rich diet.…”
Section: Introductionmentioning
confidence: 99%